Analysis Of Phishing Websites Using An Competent Feature-Based Framework (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Phishing attacks take place through various forms such as email, websites and malware. To perform email phishing, attackers design fake emails which claim to be arriving from a trusted company. They send fake emails to millions of online users assuming that at least thousands of legitimate users would fall for it. Phishing attacks are one of the most common and least defended security threats today. Objective of study to identify phishing attacks using five machine learning algorithms. The proposed system handles feature selection through learning algorithm, after feature selection, training and prediction is done. The objective of our study to find an efficient algorithm, which achieves highest accuracy.